Innovation of White Bread Colorated with Cassava Leaf as an Effort to Develop Banyuwangi Creative Industry and Tourism, Indonesia - Reni Nur Jannah Nur Jannah; Rudi Tri Handoko; Jemi Cahya Adi Wijaya (Jurnal Pariwisata Nusantara (JUWITA), 2022)
Purpose: This research aims to find recipes for white bread with cassava leaf coloring, knowing public or tourist acceptance of bread products as culinary products as an effort to develop creative industries. Method: This research was conducted by Research & Development (R&D) containing by 4 stages of development, namely Define (reference product study), Design (product design), Develop (product manufacture and testing) and Dissemination (product distribution). Result: The research method used organoleptic tests, namely the hedonic quality test and hedonic test, with ANOVA analysis showed that there were significant differences in the characteristics of color and flavor with a significant value below 0.005. The results of the analysis showed that the best treatment in terms of hedonic quality was white bread with the addition of cassava leaf coloring with a size of 12 ml based on the validation test by the two validators and proven by the hedonic quality test by 30 panelists with an average score of 3.94. Contribution: We do hope this research will be beneficial for Bnyuwangi Regency in aming their vision and mission to develop Banyuwangi Culinary Tourism